The study of aluminum loss and consequent phase transformation in heat-treated acid-leached kaolin. - Mohd Salleh, Mohamad Amran; Choo, Thye Foo; Mahmood, Che Seman (2011)
This study investigates the effect of Al leaching during Fe removal from kaolin to mullite. Heat-treated kaolin was obtained by heating natural kaolin at 400, 500, 600, 700, 800 and 900 °C. The heat-treated kaolin was then leached at 100 °C with 4 M, 3 M, 2 M, 1 M, 0.2 M solution of H2SO4 and 0.2 M solution of oxalic acid. The dried samples were sintered to 1300 °C for 4 h at a heating rate of 10 °C min−1. X-ray diffractometry and differential thermal analysis were used to study the phase transformation of kaolin to mullite. It was found that 700 °C is the optimum preheat-treatment temperature to leach out Fe and also Al for both types of the acids used. The majority of the 4 M sulfuric acid-treated kaolins formed the cristobalite phase when sintered. On the other hand, 1 M, 0.2 M sulfuric acid and 0.2 M oxalic acid leached heat-treated kaolin formed mullite and quartz phase after sintering.